ASSESSING TODDLER TEMPERAMENT USING INDONESIAN VERSION OF THUMAS AND CHESS TTS IN YOGYAKARTA (Intuisi : Jurnal Psikologi Ilmiah, 2012)
Abstract. The purpose of this study (as part thesis of Muti’ah, 2009) is assessing toddler temperament by using Thomas and Chess in Yogyakarta. Mothers of the toddlers completed the Toddler Temperament Scale (TTS) and the Socioeconomic Status. Data were collected through fill-in the TTS (toddler temperament scale) from 84 toddler respondents which were living in Yogyakarta. From the data, it was found that The TTS’ internal consistency of Indonesian toddlers was 0.653, considered acceptable and shows a high validity. The exploratory test obtained has shown that the temperament characteristic (activity, regularity, adaptability, mood approach, intensity, persistence, distractibility and threshold of Indonesia toddlers had no much different pattern compared to others countries using a similar scale. The socioeconomic effects upon the toddler behavior styles were found slightly influences in some dimensions. From the research done, this study has provided the evidence that the toddler behavioral styles were varied according to the cultural context and the characteristics of the raters (mothers). Keywords: toddler, temperament, tts